(untitled) (Research, Society and Development, 2021)
Objective: Resocialize and reduce the traumatic vulnerability of other users of health services, presenting strategies of great utility, with a suggestive approach to the contribution of child development, self-confidence, safety and comfort to these children. Methodology: This is an ecological study and review of literature that had as units of analysis the evaluation of the toy library in the reduction of childhood anxiety, especially in Brazil. The data are secondary obtained through the Notifiable Diseases Information System (SINAN). The research was based in depth on the case studies and experiences, reported in 13 articles published in the Google Scholar and Bireme databases. Results: It was found that in all articles the relationship of the recreational space has a great influence in reducing childhood anxiety and is an important pillar for the recovery and treatment of sick children. Final considerations: From these results we can conclude that, in the following work, the main approach has been a study to which a range of information extracted from the data research described on the influence and contribution to the reduction of childhood anxiety with the implementation of playrooms and games children in hospital environments, how beneficial and positive it has been for a good relationship between professional-patient, and also therapeutic in the scope of health-disease.